1990
DOI: 10.1007/bf00188110
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic regulation of circadian noradrenergic input to the chick pineal gland

Abstract: While the avian pineal gland contains circadian oscillators and photoreceptors capable of producing circadian rhythms of the hormone melatonin, it is extensively innervated by post-ganglionic fibers of the superior cervical ganglia which release norepinephrine (NE) rhythmically. Norepinephrine turnover is higher during subjective day than during subjective night. In mammals, this rhythmic input, which is higher in subjective night than subjective day, derives from the hypothalamic suprachiasmatic nuclei (SCN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 49 publications
0
38
0
Order By: Relevance
“…A HUMORAL output is thought to affect local HYPOTHALAMIC function90,110, and a neural output through SCN afferents affects CNS and peripheral sites to which they project. Among the neural output pathways is the regulation of autonomic SYMPATHETIC NERVOUS SYSTEM activity 111 , which can affect a broad range of peripheral physiological functions, including regulation of the pineal gland itself 112 . So, coordination of avian circadian outputs through the pacemakers in the pineal gland and SCN might affect many physiological outputs.…”
Section: The Circadian Clock In Birdsmentioning
confidence: 99%
“…A HUMORAL output is thought to affect local HYPOTHALAMIC function90,110, and a neural output through SCN afferents affects CNS and peripheral sites to which they project. Among the neural output pathways is the regulation of autonomic SYMPATHETIC NERVOUS SYSTEM activity 111 , which can affect a broad range of peripheral physiological functions, including regulation of the pineal gland itself 112 . So, coordination of avian circadian outputs through the pacemakers in the pineal gland and SCN might affect many physiological outputs.…”
Section: The Circadian Clock In Birdsmentioning
confidence: 99%
“…The interspecies differences concern both the ability of pineal cells in vitro to entrain their secretory activity to rapid changes in light conditions and the persistence of the endogenous oscillator activity in a continuous darkness. It has been demonstrated that also norepinephrine (NE) plays an important role in the regulation of MLT secretion in chicken and turkey pinealocytes (Cassone et al 1990, Prusik 2005, Zawilska et al 2005, Prusik and Lewczuk 2008b. It is generally accepted that NE in birds, like in mammals, is the final neurotransmitter in the multisynaptic pathway connecting the retina and the hypothalamus with the pineal organ.…”
Section: Introductionmentioning
confidence: 99%
“…one is located in the visual suprachiasmatic nuclei and influences pineal melatonin production through sympathetic innervation [11,12]; another one is located in the pineal gland itself [8,16]. In vivo experiments have suggested the presence of yet another circadian oscillator in the chicken retina that would control local melatonin production [43]; however, in vitro experiments confirming this point are still needed.…”
Section: Introductionmentioning
confidence: 99%